Java : an introduction to computer science and programming. - Savitch, Walter, ....- (Upper Saddle River, NJ : Pearson Education, 2004)
1. Introduction to Computers and Java Objects. 2. Primitive Types, Strings, and Interactive I/O. 3. Flow of Control. 4. Defining Classes and Methods. 5. More about Objects and Methods. 6. Arrays. 7. Inheritance. 8. Exception Handling. 9. Streams and File I/O. 10. Dynamic Data Structures. 11. Recursion. 12. Window Interfaces Using Swing Objects. 13. Applets and HTML. 14. More Swing.
Keywords: Java (programmeertaal).